Isolated Splenic Hydatid Disease - Alper Dilli; Idil Güneş Tatar; Umit Yasar Ayaz; Baki Hekimoglu (Case Reports in Medicine)
Hydatid disease (HD) continues to be a significant health problem in areas where animal husbandry is common but no proper veterinary control exists. The involvement of the spleen in HD is rare, and isolated splenic involvement is even less common. In this case report, we present isolated splenic HD in a 26-year-old female with complaint of abdominal pain, and we discuss some of the clinical aspects of HD. Evaluation of the patient with ultrasonography, computed tomography, and magnetic resonance imaging revealed the presence of an isolated splenic HD as a multivesicular cystic mass located near splenic hilus, measuring 12×11 cm. No other organ or system involvement could be demonstrated.